Job retention schemes during COVID-19: A review of policy responses - Werner Eichhorst; Paul Marx; Ulf Rinne; Johannes Brunner (Institute of Labor Economics (IZA), 2022)
This policy brief provides an update on job retention policies in a sample of 20 countries representing the main world regions as well as the diverse types of job retention schemes, in particular short-time work, furlough and wage subsidy schemes as they have been implemented in response to the COVID-19 pandemic. We show the diversity of these policies as well as the available information about their (re-)design as the pandemic evolved up to the most recent period. The policy brief raises main issues regarding the implementation and adaptation of job retention policies and illustrated this with four case studies.
Keywords: E24; H12; J22; J08; J65; J68; O57; 330; work; decent work; employment policy; education; skills; rapid assessment; economic recovery; economic sectors; gender equality; youth; COVID-19; survey